2020
DOI: 10.1177/1943387520910338
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Maxillofacial Trauma Patterns in the Urban Versus Suburban Environment: A Pilot Study

Abstract: Introduction: Assault appears to be the most frequent cause of facial fractures in certain urban trauma centers, possibly due to the ease of acquiring weapons and increasingly aggressive behavior. The objectives of this study were to identify specific demographic, socioeconomic, maxillofacial fracture, and assault patterns in urban versus suburban communities. Methods: A retrospective chart review of patients who sustained maxillofacial fractures from August 2014 through August 2016 at one urban campus, Einste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 33 publications
0
9
2
2
Order By: Relevance
“…Interpersonal violence is known to be one of highest causes of facial trauma in the United States and worldwide and is more pronounced in urban environments. [30][31][32] Surprisingly, the increase in assault as a mechanism at LAC +USC contrasts with a gradual decline in the number of aggravated assaults per 100,000 population in California 33 and overall crime rates in Los Angeles. 34,35 This may infer that whereas assault numbers decreased in the city, the nature and severity of remaining assaults were significantly morbid and necessitated operative intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interpersonal violence is known to be one of highest causes of facial trauma in the United States and worldwide and is more pronounced in urban environments. [30][31][32] Surprisingly, the increase in assault as a mechanism at LAC +USC contrasts with a gradual decline in the number of aggravated assaults per 100,000 population in California 33 and overall crime rates in Los Angeles. 34,35 This may infer that whereas assault numbers decreased in the city, the nature and severity of remaining assaults were significantly morbid and necessitated operative intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most interesting finding is that assault was the most common mechanism of injury overall with a rising number of attributed fractures over time. Interpersonal violence is known to be one of highest causes of facial trauma in the United States and worldwide and is more pronounced in urban environments 30–32 . Surprisingly, the increase in assault as a mechanism at LAC+USC contrasts with a gradual decline in the number of aggravated assaults per 100,000 population in California 33 and overall crime rates in Los Angeles 34,35 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a majority of orbital floor fracture patients were from the bottom 25th income quartile thus corroborating prior epidemiological facial fracture findings. [30][31][32] One possible explanation may be that low income communities residing in less safe environments may be at higher risk of orbital floor fractures. 33,34 Interestingly, Black and Latinx patients in our study had a higher prevalence of orbital reconstruction compared to their White counterparts although there was a lack of significant difference after adjustment for potential confounders.…”
Section: Discussionmentioning
confidence: 99%
“…10 In studies within the United States, assaults have also been shown to be predominant, 1,15,17 particularly in urban settings. 18 With regard to MVAs, it is not surprising that the majority of our traffic-related injuries involved pedestrians, as New York City is largely a walking city. Furthermore, the distance between Manhattan and large interstate highways brings fewer high-speed MVAs to our center.…”
Section: Mechanism Of Injurymentioning
confidence: 99%